Melatonin and its ubiquitous anticancer effects - Bhattacharya S.; Patel K.K.; Dehari D.; Agrawal A.K.; Singh S. (My University, 2025)
Melatonin (N-acetyl-5-methoxy-tryptamine), which is generally considered as pleiotropic and multitasking molecule, secretes from pineal gland at night under normal light or dark conditions. Apart from circadian regulations, Melatonin also has antioxidant, anti-ageing, immunomodulation and anticancer properties. From the epidemiological research, it was postulated that Melatonin has significant apoptotic, angiogenic, oncostatic and anti-proliferative effects on various oncological cells. In this review, the underlying anticancer mechanisms of Melatonin such as stimulation of apoptosis, Melatonin receptors (MT1 and MT2) stimulation, paro-survival signal regulation, the hindering of angiogenesis, epigenetic alteration and metastasis have been discussed with recent findings. The Melatonin utilization as an adjuvant with chemotherapeutic drugs for the reinforcement of therapeutic effects was also discussed. This review precisely emphasizes the anticancer effect of Melatonin on various cancer cells. This review exemplifies the epidemiology and anticancer efficiency of Melatonin with prior attention to the mechanisms of actions. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.